Metabolic, genetic and physiological responses to SO2 exposure and nutrient-limiting conditions in Brettanomyces bruxellensis - Louw, Marli (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.